KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS LINGKUNGAN SEBAGAI PENGUATAN PENDIDIKAN HUMANISTIK DI SEKOLAH ADIWIYATA - Atiqoh, Layly; Saputro, Budiyono (EDUKASIA, 2017)
ISLAMIC EDUCATION CURRICULUM BASED ON ENVIRONMENT AS A REINFORCEMENT FOR HUMANISTIC EDUCATION IN ADIWIYATA SCHOOL. The main objectives of this study are to describe planning, development,   implementation, a success and special quality of Islamic education environment based curriculum on Adiwiyata school SMPN 6 & SMPN 7 Salatiga. The research method is qualitative research. This research was conducted at Adiwiyata school SMPN 6 & SMPN 7 Salatiga. The main subjects of this study are the headmaster, the school committee, the vice principal, areas of curriculum, Head of Adiwiyata, teachers, and students. The technique of collecting data is by observating, interviewing, and documenting. The results of this study are the school has been: (1) planning  the  Islamic  education  environment  based  curriculum  by conducting mapping of basic competencies to be an indicator, (2) carried out the development of the Islamic education environment based curriculum is integrated to the material and the   environment,  (3)   implemented   the   Islamic   education   environment based curriculum by creating an annual planning, communicating to other stakeholders and teachers design the implementation of learning and assessment, (4) the special quality of the students is that they care about the environment around as a strengthening of humanistic education.